2019
DOI: 10.1002/jcb.29478
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide screening and cohorts validation identifying novel lncRNAs as prognostic biomarkers for clear cell renal cell carcinoma

Abstract: s Clear cell renal cell carcinoma (ccRCC) is the main subtype of renal cell carcinoma with varied prognosis. We aimed to identify and assess the possible prognostic long noncoding RNA (lncRNA) biomarkers. LncRNAs expression data and corresponding clinical information of 619 ccRCC patients were downloaded from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. Differentially expressed genes analysis, univariate Cox regression, the least absolute shrinkage and selection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…More importantly, we not only constructed a 13-lncRNA-based risk score model with moderate accuracy, but also identified six independent adverse prognostic lncRNAs for patients with ccRCC, including lncRNA AC009654.1, AC012615.3, AC092490.2, AL357507.1, LINC01234 and LINC01956. It was similar to a recent study which suggested that lncRNA AC009654.1, AC092490.2, LINC00524, LINC01234 and LINC01885 were significantly associated with ccRCC prognosis (Zhang et al, 2020). The expression levels of the six lncRNAs above were upregulated in ccRCC tissues and the high expression levels of them predicted a worse OS in ccRCC patients.…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, we not only constructed a 13-lncRNA-based risk score model with moderate accuracy, but also identified six independent adverse prognostic lncRNAs for patients with ccRCC, including lncRNA AC009654.1, AC012615.3, AC092490.2, AL357507.1, LINC01234 and LINC01956. It was similar to a recent study which suggested that lncRNA AC009654.1, AC092490.2, LINC00524, LINC01234 and LINC01885 were significantly associated with ccRCC prognosis (Zhang et al, 2020). The expression levels of the six lncRNAs above were upregulated in ccRCC tissues and the high expression levels of them predicted a worse OS in ccRCC patients.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we firstly identified DEGs as candidate genes for the ceRNA network by using the DESeq 2 method, which has better statistical power in sensitivity and precision than edgeR and DESeq. To the best of our knowledge, our study is the first to use the DESeq 2 method in constructing the ceRNA network in KIRC, resulting in an inconsistent finding in the DEGs screen with other studies [35,43]. Since the lncRNA-miRNA-mRNA interaction in the ceRNA network only presented in the cytoplasm [44], we excluded the lncR-NAs that only located in the nucleus to enhance the accuracy of prediction.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the heterogenous nature of kidney cancer (Sankin et al, 2014), single biomarker lacks ample credibility to predict patients' outcomes, thereby, an RS that is composed of more than one biomarker is necessary. There were a few former articles about ccRCC and RS models which were based on gene expression (Zeng et al, 2019;Li et al, 2018), lncRNA expression (Liu et al, 2018;Zhang et al, 2019) or miRNA expression (Luo et al, 2019;Fritz et al, 2014), because of the tremendous amount of genes and various RNAs the models of these studies were diverse. Currently, as the importance of m6A cut a striking figure, despite the fact that the first report of m6A was as early in 1974 (Desrosiers, Friderici & Rottman, 1974), it was not until recent days that the mechanism of the m6A was uncovered (Roundtree et al, 2017).…”
Section: Discussionmentioning
confidence: 99%